THE VALIDITY OF STUDENT WORKSHEET BASED ON READING, QUESTIONING AND ANSWERING (RQA) MODEL IN INVERTEBRATE MATERIAL FOR TRAINING CRITICAL THINKING SKILL FOR SENIOR HIGH SCHOOL STUDENT - Nuzulah, Dewi Firdausi; Budijastuti, Widowati (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2018)
AbstractCritical thinking is a process directed in solving problems and become a much-needed ability to make students better prepared in the learning process. Critical thinking skills in learning proces needs to be facilitated bysuitable appropiate teaching materials that isstudent worksheet based on Reading, Questioning and Answering (RQA) model.RQA learning model is a learning model which train student in construct their own knowledge so the students not only getting the concept but understand the material critically. One of the alternatives to help students to understanding material by facilitating student worksheet to train studentâ€™s critical thinking skill.The research was intended to describe the validity of student worksheet based on RQA model in Invertebrate material for train critical thinking skill senior high school student. This research was a developmental research was done based on 4-D model which modified to 3-D model (Define, Design, develop). Validation results indicate that the developed of student worksheet was categorized very valid with the percentage reaches 95,13%.Â Keywords: Student Worksheet, RQA model, Critical Thinking Skill, Invertebrate